Analisis Makna Kata Ageru, Kureru, Morau dalam Kalimat Bahasa Jepang - Igat Meliana; Dhea Savitri (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
Ageru (あ げ る) and Kureru (く れ る) Verbs mean "to give", while Morau (も ら う) verb means "to receive". The reaserch problem is the meaning of Ageru (あ げ る), Kureru (く れ る), Morau (も ら う) verbs that used on depending on who gives and who receives whether the closest person to the speaker (relative) or outside the scope of the speaker (other people). The method used is descriptive literature. The purpose of this study was to determine the meaning of the words Ageru, Kureru, Morau, the use of Ageru, Kureru, Morau, and the differences between Ageru, Kureru and Morau. The results of the analysis concluded that: 1. Ageru (あ げ る) which means "to give" where the first person is the speaker, to a scope far from the speaker. 2. Kureru (く れ る) which means "to give" where the second person gives to the first person (speaker), the flow of the object / gift approaches from outsiders to the speaker or relatives of the speaker. 3. Morau (も ら う) which means "to accept" is general in nature anyone can use it as an expression of acceptance of something from someone.